Do Surges in Civil Mobilization Serve as Early Warnings for Political Conflict? - Michael Haratua Rajagukguk; Ruben Cornelius Siagian (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2026)
Political conflict and mass violence are major threats to security stability, especially in developing countries such as Indonesia. Civil mobilization through demonstrations is often considered an expression of social dissatisfaction, but its role as an early indicator of political violence escalation has not been analyzed quantitatively across countries and time. This study aims to explore the temporal relationship between an increase in demonstrations, the escalation of political violence, and the number of fatalities, as well as to develop an Early Warning Index as a counterintelligence tool. Using cross-country ACLED panel data from 1997 to 2026, the study applies a fixed effects model with one and two period lags, logarithmic transformation, and Granger causality tests to assess temporal causal relationships. The results show that a surge in demonstrations in the previous period significantly predicts an increase in political violence (coefficient = 0.592, t = 11.62, p < 0.001) and fatalities (coefficient = 0.475, t = 6.90, p < 0.001). The Granger causality test confirmed that demonstrations systematically led to an escalation in violence and fatalities. The Early Warning Index shows significant variations in risk, with maximum values indicating high social pressure that can serve as an early signal of conflict escalation. These findings fill a gap in quantitative research on the role of demonstrations as a leading indicator of political conflict. The index provides counterintelligence decision makers with an analytical tool for proactively detecting the risk of destabilization, particularly in the pre-election period or when sensitive identity-based issues arise.